LncRNA-OG Promotes the Osteogenic Differentiation of Bone Marrow-Derived Mesenchymal Stem Cells Under the Regulation of hnRNPK. (17th November 2018) - Tang, Su'an; Xie, Zhongyu; Wang, Peng; Li, Jinteng; Wang, Shan; Liu, Wenjie; Li, Ming; Wu, Xiaohua; Su, Hongjun; Cen, Shuizhong; Ye, Guiwen; Zheng, Guan; et al.
Abstract : Bone marrow-derived mesenchymal stem cells (BM-MSCs) are the main source of osteoblasts in vivo and are widely used in stem cell therapy. Previously, we analyzed long noncoding RNA (lncRNA) expression profiles during BM-MSC osteogenesis, and further investigation is needed to elucidate how lncRNAs regulate BM-MSC osteogenesis. Herein, we used customized microarrays to determine lncRNA expression profiles in BM-MSCs on days 0 and 10 of osteogenic differentiation. In addition, we identified a novel osteogenesis-associated lncRNA (lncRNA-OG) that is upregulated during this process. Functional assays showed that lncRNA-OG significantly promotes BM-MSC osteogenesis. Mechanistically, lncRNA-OG interacts with heterogeneous nuclear ribonucleoprotein K (hnRNPK) protein to regulate bone morphogenetic protein signaling pathway activation. Surprisingly, hnRNPK positively regulates lncRNA-OG transcriptional activity by promoting H3K27 acetylation of the lncRNA-OG promoter. Therefore, our study revealed a novel lncRNA with a positive function on BM-MSC osteogenic differentiation and proposed a new interaction between hnRNPK and lncRNA. Stem Cells 2018 Stem Cells 2019;37:270–283 : Abstract : (A): During the osteogenesis of bone marrow-derived mesenchymal stem cells, osteogenesis-associated long noncoding RNA interacts with hnRNPK to promote the expression of bone morphogenetic proteins family, which ultimately promotes the process of osteogenesis. (B): Interestingly, hnRNPK can also bind to the promoter of osteogenesis-associated long noncoding RNA, promoting osteogenesis-associated long noncoding RNA transcriptional activity by increasing histone H3 lysine 27 acetylation (H3K27ac).